Monitoring User-Based Accessibility Assessment in Urban Environments and in Public Buildings - Stauskis, Gintaras (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The research features analysis of user-experience-based accessibility assessment and progress monitoring of buildings and public spaces; this analysis is used as a tool for facilitating the development of humane, socially sustainable and an inclusive urban environment. A group of users representing people with different kinds of disabilities, the elderly and families with children was created to assess the quality of access to various buildings with different functions and locations across Vilnius and in Singapore. A school, two hospitals, a rehab centre and two offices were selected for access monitoring in Vilnius City, while a hotel, a café and two metro stations with public squares were chosen for access assessment in Singapore. As the same method was principally applied to assess accessibility of selected buildings in Vilnius City in 2000 and 2017 and in Singapore in 2012, the article draws a comparative analysis of access levels in these two cities located in different global regions. The results show a definite improvement of access quality over time and also identify the critical aspects in this process. The segment of plot planning represents the lowest quality of access for all assessed building types as compared to the building segment and the external–internal element segments. The paper also draws conclusions that access improvement is a continuous process of implementing advanced urban policy instruments, and city planners can contribute to it by constantly analysing and presenting to public the monitoring data about the progress in access improvement. Comparing the assessment results between Vilnius City and Singapore – cities that are located in different global regions and in different socio-economic environments – provides a practical tool for benchmarking and setting the priorities for this process.